Back Cover: Carbon dots: An innovative luminescent nanomaterial. Issue 3 (24th June 2022) - Shi, Yuxin; Xu, Huimin; Yuan, Ting; Meng, Ting; Wu, Hao; Chang, Jianqiao; Wang, Haoyu; Song, Xianzhi; Li, Yunchao; Li, Xiaohong; Zhang, Yang; Xie, Wenjing; et al.
Abstract : Carbon dots (CDs) attract a mounting interests as readily accessible, nontoxic, and relatively inexpensive carbon‐based nanomaterials. This review systematically summarizes the recent developments in the structural design of CDs, including internal carbon core and external carbon shell, and related optical properties from singlet and triplet states. Their practical applications in optoelectronic devices and biology are also highlighted.